Time-consistent resource management with regime shifts - Maria Arvaniti; Chandra K. Krishnamurthy; Anne-Sophie Crépin (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
We investigate how a resource user who is present-biased manages a renewable resource stock with variable growth that could undergo a reversible regime shift (an abrupt, persistent change in structure and function of the ecosystem supplying the resource). In a discrete-time quasihyperbolic discounting framework with no commitment device, and using only generic utility functions and stock transition with regime shifts, we show that there is a unique, time-consistent stationary Markov-Nash equilibrium extraction policy. Further, we find that the optimal extraction policy is increasing in the resource stock and in the degree of present bias. Overall, our results suggest that for characteristics of ecosystems commonly considered in the literature, presentbiased resource users will increase extraction when faced with regime shifts.
Keywords: Q20; C61; C73; 330; Renewable resources; Regime shifts; Hyperbolic Discounting; Present bias; Uncertainty; Markov Equilibrium